Why do people play games on mobile commerce platforms? An empirical study on the influence of gamification on purchase intention. (January 2022) - Yu, Na; Huang, Yi-Ting
Abstract: In recent years, there has been an upsurge in the number of mini-games on mobile commerce platforms. The emerging gamification phenomenon of e-commerce still requires theory and investigation in order to supplement its explanation. This study aims to explore the intention of users to play games on mobile commerce platforms, as well as the influence of gamification mechanisms on users' purchase intentions on these platforms. From the perspective of perceived value theory, data from 1586 mobile commerce shoppers in China were collected and analyzed using a structural equation model. The results of the study found that utilitarian value, hedonic value, and social value are positively correlated with game use intention, while spending less time/energy also positively affects game use intention. These games are more attractive to women. The usage rate of games and the average monthly spending amount on a mobile commerce platform are both positively correlated with users' purchase intentions on the platform. Highlights: Mobile commerce users play mini-games because they gain fun with less time spending. Gamification has a positive impact on the purchase intentions of users who access mobile commerce platforms. Utilitarian, hedonic, and social value positively influence users to play games on mobile commerce platforms. Mini-games on mobile commerce platforms are more attractive to women.